Gemcitabine-docetaxel therapy in pediatric patients with relapsed or refractory sarcoma: a single-center experience - Çil, Metin; Yağcı, Begül Ganiye (Frontiers in Pediatrics, 2026)
BackgroundThe prognosis for pediatric patients with relapsed or refractory sarcoma remains poor, and standard salvage therapies are lacking. This study evaluated the efficacy and toxicity of the gemcitabine and docetaxel (GEMDOX) combination in this patient population.MethodsWe retrospectively analyzed 36 pediatric patients treated with GEMDOX at our institution between 2015 and 2025. Patients received gemcitabine (1,000 mg/m2 on days 1 and 8) and docetaxel (100 mg/m2 on day 8) in 21-day cycles.ResultsThe median age was 13.5 years, with osteosarcoma being the most common diagnosis (58.3%). GEMDOX was administered predominantly as a third-line regimen (58.3%). The objective response rate (ORR) at the final assessment was 5.8%, and the disease control rate (DCR) was 14.6%. The median progression-free survival (PFS) and overall survival (OS) were 5.72 months (95% CI, 3.95–7.48) and 12.33 months (95% CI, 8.97–15.66), respectively. The most common Grade 3–4 toxicities were neutropenia (22.2%) and febrile neutropenia (19.4%), both of which were manageable with G-CSF support. No treatment-related mortality occurred.ConclusionsAlthough the objective response rate was modest in this heavily pretreated cohort, GEMDOX demonstrated a manageable safety profile. It represents a viable palliative option with a manageable toxicity profile for pediatric patients with relapsed/refractory sarcoma when curative options are limited. However, given its intensive nature, optimal efficacy may be better achieved when utilized earlier in the relapse setting rather than as a late-line rescue therapy.